2018
DOI: 10.1016/j.pbiomolbio.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping cardiomyopathy in adult zebrafish

Abstract: Hypertrophic cardiomyopathy (HCM) is usually manifested by increased myofilament Ca sensitivity, excessive contractility, and impaired relaxation. In contrast, dilated cardiomyopathy (DCM) originates from insufficient sarcomere contractility and reduced cardiac pump function, subsequently resulting in heart failure. The zebrafish has emerged as a new model of human cardiomyopathy with high-throughput screening, which will facilitate the discovery of novel genetic factors and the development of new therapies. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 91 publications
(247 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, gtpbp3 −/− adult zebrafish displayed the hypertrophy of cardiac myocytes and myocardial fiber disarray in ventricles. These cardiac defects in gtpbp3 −/- zebrafish recapitulated the clinical phenotypes in HCM patients carrying the GTPBP3 mutations (32,91–93). These data demonstrated that the gtpbp3 -deletion-induced mitochondrial dysfunctions caused hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, gtpbp3 −/− adult zebrafish displayed the hypertrophy of cardiac myocytes and myocardial fiber disarray in ventricles. These cardiac defects in gtpbp3 −/- zebrafish recapitulated the clinical phenotypes in HCM patients carrying the GTPBP3 mutations (32,91–93). These data demonstrated that the gtpbp3 -deletion-induced mitochondrial dysfunctions caused hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 60%
“…The zebra fish (Danio rerio) model remains one of the most effective technologies for discovering and functional studying novel cardiomyopathy candidate genes, especially the ability to use morpholino knockdown techniques in fish models [26,41,42]. Compared with other vertebrate models, the zebra fish embryos are transparent allowing genetic engineering approaches to apply fluorescent reporter transgenes with genetic fate mapping strategies combined with high-resolution, high-throughput microscopy imaging in vivo of the heart [43,44].…”
Section: Genetically Engineered Animal Models Of Cardiomyopathymentioning
confidence: 99%
“…Because a zebrafish heart is only sized about 1-2 mm in diameter, novel phenotyping toolkits, such as high-frequency echocardiography, the Langendorff ex vivo system, ECG, and single-myofibril contractility analysis, have been developed to define progression of cardiac remodeling in zebrafish (Dvornikov et al, 2014;Lin et al, 2015;Koth et al, 2017;Merrifield et al, 2017;Wang et al, 2017;Stoyek et al, 2018;Zhang et al, 2018;Wakamatsu et al, 2019;Yan et al, 2020). Because these toolkits have already been comprehensively reviewed recently (Dvornikov et al, 2018;Lin et al, 2020), we only list some new techniques in Table 2. Partially because these new technologies are not readily accessible, many published adult zebrafish inherited cardiomyopathy models have not been sufficiently phenotyped to be categorized into a certain type of cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%